COMPARATIVE STUDY OF SINGLE SURFACE AND DOUBLE SURFACE PHOTOTHERAPY IN NEONATAL HYPERBILIRUBINEMIA - AKHIL, CHITTURI VENKATA SAI; DAMKE, SACHIN (International Journal of Psychosocial Rehabilitation, 2020)
Neonatal jaundice occurs in about 60% of full-term neonates and in about 80% of preterm neonates. A significant proportion of causes of hyperbilirubinemia in the term newborn are benign and reversible. However, considering the potentially irreversible toxicity of bilirubin on the central nervous system (kernicterus), newborns must be evaluated to identify which ones will need treatment.It is a result of the increased breakdown of RBC and/or decreased hepatic excretion of bilirubin. Generally NNH is a natural transition that resolves within the 1st week of life with liver maturity. Since the 1950s, phototherapy has been the therapy of choice for the newborn with indirect hyperbilirubinemia. Single phototherapy (SP) is the most commonly used method, and, when bilirubin levels are close to the threshold for exchange transfusion, intensive phototherapy is indicated6. To study and compare the rate of fall of Total Serum Bilirubin levels in neonatal hyperbilirubinemia treated with Single Surface Phototherapy and Double Surface Phototherapy. Neonates in NICU and in Postnatal wards, who are clinically icteric, will be enrolled in the study after written informed consent from the parents(Annexure 1). Data will be collected in a pre-decided proforma(Annexure 2). Details will be obtained from direct questioning of the mother and examination of the newborn and his record. Repeat bilirubin levels will be estimated as per the protocols and requirements of the NICU. Phototherapy will be stopped in accordance with the protocols followed in NICU. The rate of fall of serum bilirubin levels will be observed in both the types of phototherapy given to determine if there is any difference in the effectiveness of SSPT vs DSPT. DSPT is more effective than SSPT. Conclusions of the study will be based on the results of the study.